2007
DOI: 10.3892/or.18.3.691
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Wnt pathway components frizzled and disheveled in colon cancer arising in patients with inflammatory bowel disease

Abstract: Mutations in apc which lead to activation of the Wnt signaling pathway are a hallmark of sporadic colon cancers but occur infrequently in colon cancers arising in patients with inflammatory bowel disease (IBD). There is evidence, however, that other components of the Wnt pathway may be altered in IBD-related colon cancer. In this study, we examined the expression the Wnt pathway components frizzled (Fz), the cell surface receptor, and disheveled (DVL), a family of cytoplasmic signal transduction molecules, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
0
29
1
1
Order By: Relevance
“…Colonic mucosal proliferation is increased in UC, especially in the setting of high-grade dysplasia [26]. However, whereas some studies have suggested that Wnt signaling is involved in UC-related colon cancer [23], others suggest that UC-associated colon cancers arise along a different pathway than sporadic, Wnt/ APC driven, colon cancers [27]. Characteristics of Wnt signaling in UC mucosa compared with colonic mucosa of non-UC patients has not been previously defined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Colonic mucosal proliferation is increased in UC, especially in the setting of high-grade dysplasia [26]. However, whereas some studies have suggested that Wnt signaling is involved in UC-related colon cancer [23], others suggest that UC-associated colon cancers arise along a different pathway than sporadic, Wnt/ APC driven, colon cancers [27]. Characteristics of Wnt signaling in UC mucosa compared with colonic mucosa of non-UC patients has not been previously defined.…”
Section: Discussionmentioning
confidence: 98%
“…Nucleotide array analysis comparing inflamed intestinal mucosa of patients with ulcerative colitis to inflamed mucosa of patients with Crohn's disease revealed increased expression of three Wnt pathway genes, SARP1 (SFRP2), frizzled (FZD), and disheveled (DVL), in samples from patients at highest risk for colon cancer-those with longstanding ulcerative colitis [22]. Recent work from our laboratory indicates that the pattern of DVL family-member expression is distinct in IBDassociated colon cancers in comparison with sporadic colon cancer [23]. Differential expression of FZD, DVL, and SFRP2 suggests that Wnt signaling may contribute to colon carcinogenesis in patients with IBD.…”
Section: Introductionmentioning
confidence: 95%
“…In closing, while cellular descriptions and molecular signals that control cell proliferation and cell mutations during carcinogenesis in UC have received much attention ( [35][36][37][38][39][40], the signals that might be instrumental in designing morphogenesis (41) resulting in the "etching" of various CCC phenotypes in UC, have remained unattended.…”
Section: Discussionmentioning
confidence: 99%
“…В исследо-вании пути сигнала Wnt, который был опосредован через β-катенин/Tcf-4, было показано, что он может быть ключевым регулирующим каналом для диффе-ренцировки клеток Панета и вызвать их созревание в криптах кишечника [174,233]. В сравнительных ис-следованиях было продемонстрировано, что генная программа клеток Панета критически зависит от ак-тивности эмбрионального фактора Tcf-4 кишечни-ка [213]. Этот сигнальный путь нарушен у пациентов IBD.…”
Section: патогенетическое значение дефенCинов при инфекционных процессахunclassified